Open-Loop Switched-Capacitor Integrator for Low Voltage Applications - Stefano D’Amico (Electronics, 2020)
An architecture of a switched-capacitor integrator that includes a charge buffer operating in an open-loop is hereby proposed. As for the switched-capacitor filters, the gain of the proposed integrator, which is given by the input/output capacitor ratio, ensures desensitization to process, voltage, and temperature variations. The proposed circuit is suitable for low voltage supplies. It enables a significant power saving compared to a traditional switched-capacitor integrator. This was demonstrated through an analytical comparison between the proposed integrator and a traditional switched-capacitor integrator. The mathematical results were supported and verified by simulations performed on a circuit prototype designed in 16 nm finFET technology with 0.95 V supply. The proposed switched-capacitor integrator consumes 76 µW, resulting in more than twice the efficiency for the traditional closed-loop switched-capacitor filter as an input voltage equal to 31.25 mV at 7 ns clock period is considered. The comparison of architectures was led among the proposed integrator and the state-of-the-art technology in terms of the figure of merit.